The initial study on user awareness regarding JAKIM's halal certification / Zuraida Othman @ Salleh - Othman @ Salleh, Zuraida (Faculty of Information Technology and Quantitative Sciences, 2005)
Halal food is gaining in popularity worldwide as more and more people become aware of the Islamic food requirements. This popularity is not only driven by the awareness amongst Muslims of the need that which is believed halal but also from manufacturers and suppliers who want to tap into lucrative Muslims markets. This research paper will discuss about the user awareness regarding JAKIM's halal certification. Basically, the purpose of this research is to measure degree on user awareness of JAKIM's halal Certification in food industry and also to propose practical guidelines for halal certification that can be implemented by JAKIM. The researcher has conducted interview with respondents who carmot read the questionnaire that was provided. Besides, to investigate and gathered the information the questionnaire was distributed to consumers in a few areas. Then, those data were analyzed and tabulated in form of bar chart and pie chart to get the clear picture of overall general and specific about halal certification. Results show that majority of respondents fix)m 136 respondents are aware about the importance of using halal certification in food industry. The level of consumer awareness is high because consumers nowadays preferred halal product even they are non Muslims consumer. It because they like to eat hygienic food compared to unlawfiil food. The data is analyzed by using SPSS version 11.0 and Microsoft Excel. In addition, the hypothesis for this research is there are relationship between awareness of halal certification and their perception about the importance of halal certification implementation.